Correction: Transcriptomics analysis of the bovine endometrium during the perioestrus period. - Mohammed A Alfattah; Carolina N Correia; John A Browne; Paul A McGettigan; Katarzyna Pluta; Stephen D Carrington; David E MacHugh; Jane A Irwin (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0301005.].